2007
DOI: 10.1179/acb.2007.036
|View full text |Cite
|
Sign up to set email alerts
|

A Belgian Registry of Interleukin-2 Administration for Treatment of Metastatic Renal Cell Cancer and Confrontation With Literature Data

Abstract: In an effort to map the use of interleukin-2 (IL-2) treatment in patients with clear cell renal cell cancer (RCC) in Belgian hospitals, 44 cases were registered from 9 hospitals between February 2003 and June 2006. It was demonstrated that the majority of these patients were treated with subcutaneous (SC) IL-2. Other methods such as the inhalation of the drug in case of intrathoracic disease or high dose intravenous (IV) administration were much less frequent (3 and 0 cases in this registry, respectively). The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2010
2010

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…, 2007). The therapeutic effectiveness of IL‐2, widely used in oncology, is generally considered significant but rather low (Bambust et al. , 2007).…”
Section: Cytokine and Anti‐cytokine Therapiesmentioning
confidence: 99%
“…, 2007). The therapeutic effectiveness of IL‐2, widely used in oncology, is generally considered significant but rather low (Bambust et al. , 2007).…”
Section: Cytokine and Anti‐cytokine Therapiesmentioning
confidence: 99%
“…The outlook from cases using IL‐2 cytokine treatment is not much better with a median survival period of approximately 10 months [3] and a 5‐year survival rate of <10%[4]. In addition, many studies have suggested that the use of a high dose of IL‐2 results in toxicity and thus, limits the applicability of the cytokine to RCC patients [5, 6].…”
Section: Introductionmentioning
confidence: 99%